THE PDCA CYCLE IN DECISION MAKING - Bemi, Hector Aparecido; Souza Junior, Marco Antonio Alves de (Revista Interface Tecnológica, 2021)
The use of the PDCA Cycle management tool has been in common and strategic use in organizations, it is used to improve production processes and better responses in decision making. In this study, this tool was used to identify and make decisions to solve losses that occurred in the company's production methods. The theoretical basis with bibliographic research was also used. Where the efficiency and importance of using the PDCA cycle was proven and when it contributes to organizations.
Keywords: PDCA; Productivity; Quality management; Management tools